PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI DARING TERHADAP KEPUTUSAN PEMBELIAN KEMBALI AYAM KOPLO TEBET, JAKARTA SELATAN - Ignatius Stefanus Manogi Kevin; Darwin Raja Unggul Saragih (Nusantara Hasana Journal, 2022)
This research aims to analyze the influence of product quality, price perception and promotion on the repurchase decision of Ayam Koplo Tebet, South Jakarta. This study used the purposive sampling method with a total of 100 research samples. Data collection is carried out using questionnaires. The primary data obtained from the study were then analyzed using multiple linear regression test tools using the help of SPSS 25. The results of this study show that product quality, price perception, and online promotion partially influence the decision to repurchase Ayam Koplo Tebet, South Jakarta. And the results of the analysis together show that product quality, price perception, and online promotion have a positive effect on the repurchase decision of Ayam Koplo Tebet, South Jakarta.